‘Per aurem intrat Christus in Mariam’. An Iconographic Approach to the ‘conceptio per aurem’ in Italian Trecento Painting from Patristic and Theological Sources: Aproximación iconográfica a la conceptio per aurem en la pintura italiana del Trecento desde fuentes patrísticas y teológicas - Salvador González, José María (De Medio Aevo, 2016)
The mariological thesis of the conceptio per aurem, according to which the Virgin Mary would have conceived Jesus Christ trough the ear at the instant of hearing the angel’s heavenly message announcing her that she would be mother of the Son of God incarnate without losing her virginity, has received so far very few academic studies rigorously grounded in primary sources. In fact the references to this theory in the specialized literature are very scarce and, when a scholar evokes it, he almost always only alludes to it, without providing documentary evidence. However, as the nine Italian paintings discussed here reveal, this theory was illustrated by subtle visual metaphors in many medieval paintings, which were inspired by a strong literary tradition. In addition a pleiad of Church Fathers and medieval theologians testify, by explicit statements, that such a theory enjoyed remarkable acceptance among teachers of Christian thought. Based on many patristic and theological texts, this paper attempts two main purposes: firstly, to expose the various theoretical formulations proposed by these thinkers; then to try to highlight the dogmatic meanings that underlie this astonishing thesis.